Exploring the local economic development initiatives for unemployed rural women in Mandeni municipality - Dhlodhlo, Lindelani Mkhumbuzi (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.